Historicizing Korean teacher professionalism and the making of a professional Confucian teacher. Issue 3 (4th May 2022) - Kim, Ji-Hye
ABSTRACT: The purpose of this paper is to historicize the traveling idea of teacher professionalism in the context of South Korea and to investigate how the idea is culturally translated and negotiated together with the traditional notion of a teacher. In doing so, this paper problematizes the modern idea of 'teachers as professionals' and its translation through the idea of territorialization. The investigation on the modern episteme of teachers revealed the colonialization of modernization as scientization. In doing so, multiple classifications and ordering practices occurred in the making of professional teachers as a particular kind of people were discussed. Simultaneously, the study also made clear that the traditional episteme has not disappeared nor simply westernized. Rather, the result showed that the modern understanding of a teacher was re-territorialized with traditional episteme and it created new subjectivities of Korean teachers as professional Confucian teachers.